Nutritious characteristics of a liquid silage from baby banana (Musa acuminata AA) with taro tubers (Colocasia esculenta (L) Schott) and its effect on post-weaning pigs - Caicedo, Willan (2020)
The aim of this study was to evaluate the use of liquid silage of baby banana with taro tubers in the diet of post-weaning pigs. In experiment 1, 30 microsilos of 1 kg capacity were prepared and physical, microbiological, organoleptic and chemical characteristics were determined at 1, 4, 8, 15, 30 and 60 days of fermentation (five per day). In experiment 2, 60 Landrace x Duroc x Pietrain castrated piglets of 8.53 ± 0.28 kg were used, distributed in three groups with 20 animals each and fed with 0, 2 and 4% silage inclusion in the diet. The silage on day 1 had the highest temperature (22.56 °C) and pH (4.82). There was no presence of Escherichia coli, Clostridium spp or Salmonella spp. The odour (fermented sweet), colour (light greenish) and consistency (pasty) of the silage was adequate. In addition, it presented a good content of dry matter, organic matter, protein, nitrogen-free extracts, gross energy, digestible energy, metabolizable energy and low levels of ashes, fat and fibre. The inclusion of 2 and 4% liquid silage of banana orito with taro tubers in the diet of post-weaning pigs improved feed consumption, bodyweight gain, feed conversion, final body weight and reduced the incidence of diarrhoea in animals.